1942
DOI: 10.1084/jem.75.4.395
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Purification of Poliomyelitis Virus

Abstract: The application of high speed differential centrifugation to the purification of poliomyelitis virus has been a logical step since Stanley and Wyckoff (1) showed that relatively small and unstable plant viruses could be isolated as homogeneous materials by this method. The sedimentation of poliomyelitis virus in an ultracentrifuge was first demonstrated by Schultz and Raffel (2), and more recently Clark, Rasmussen, and White (3) obtained sediments which showed an irregular but in some instances high virus ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1948
1948
1958
1958

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 4 publications
1
0
0
Order By: Relevance
“…Electron micrographic studies of this purified preparation by GoLLAN and MARVIN (1948) showed uniform particles in the range from 10-12 mf1, with an average diameter of about 12 IDf1. These findings are in agreement "\\<ith the early measurements of purified LANSING poliomyelitis virus by LORING et al (1942;. However, the question arises whether the observed particles were really the infectious unit or the smaller component which is currently thought to be associated with the complement-fixing property of polioinyelitis virus.…”
Section: Morphology Of Virus (Electronmicroscopy Ultrafiltration Usupporting
confidence: 83%
“…Electron micrographic studies of this purified preparation by GoLLAN and MARVIN (1948) showed uniform particles in the range from 10-12 mf1, with an average diameter of about 12 IDf1. These findings are in agreement "\\<ith the early measurements of purified LANSING poliomyelitis virus by LORING et al (1942;. However, the question arises whether the observed particles were really the infectious unit or the smaller component which is currently thought to be associated with the complement-fixing property of polioinyelitis virus.…”
Section: Morphology Of Virus (Electronmicroscopy Ultrafiltration Usupporting
confidence: 83%